Portrait of the Use of Indonesian of Factory Workers in Pekalongan Regency - Diyan Larasati; Sri Suciati; Muhajir Muhajir (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study aims to provide a comprehensive portrayal of Indonesian language utilization among factory workers in Pekalongan Regency. Employing a descriptive qualitative approach, the research investigates the factors influencing language preference and usage within this community. Data collection methods include documentation, questionnaires, and interviews, with analysis conducted through proficient engagement listening techniques. The findings reveal a nuanced interplay of factors shaping language behavior among factory workers. While Indonesian emerges as the dominant language in the workplace, driven by professional demands and the need for intercultural communication, the use of regional languages, particularly Javanese, persists in daily interactions. Notably, this linguistic landscape is influenced by factors such as workplace dynamics, societal norms, and generational shifts. By shedding light on these patterns, the study contributes to our understanding of language dynamics within industrial settings and highlights the importance of sociolinguistic factors in shaping communication practices.